Identification and structure elucidation of a new degradation impurity in the multi-component tablets of amlodipine besylate - Gibala, Petr; Douša, Michal; Kalužíková, Aneta; Tkadlecová, Marcela; Štefko, Martin; Kalášek, Stanislav; Břicháč, Jiří (Journal of pharmaceutical and biomedical analysis, 2019)
New unknown impurity at m/z 421.15 was observed during the accelerated stability analysis (40 °C/75% relative humidity) in the multi-component tablets of amlodipine besylate by reversed-phase ultra-high performance liquid chromatography-mass spectrometry (UHPLC-MS). UHPLC-MS and nuclear magnetic resonance (NMR) techniques were employed to identify and fully characterize the degradation compound. The degradation product was unambiguously identiﬁed as 3-ethyl 5-methyl 4-(2-chlorophenyl)-6-methyl-2-(morpholin-2-yl)-1,4-dihydropyridine-3,5-dicarboxylate and mechanism of its formation was proposed. It was confirmed that the degradation product was formed by the reaction of amlodipine with formaldehyde originating from the excipients present in the dosage form.
Keywords: valsartan; Chromatography, High Pressure Liquid; farmaceutická chemie; formaldehyd; Drug Stability; Chromatography, Reverse-Phase; Valsartan; fixní kombinace léků; pomocné látky; UHPLC–MS; amlodipin; Amlodipine; Excipients; Drug−excipient interactions; magnetická rezonanční spektroskopie; Hydrochlorothiazide; chromatografie s reverzní fází; molekulární struktura; kontaminace léku; Drug Contamination; časové faktory; Molecular Structure; hmotnostní spektrometrie s elektrosprejovou ionizací; hydrochlorthiazid; stabilita léku; Chemistry, Pharmaceutical; Spectrometry, Mass, Electrospray Ionization; Structural elucidation; Magnetic Resonance Spectroscopy; Drug Combinations; Time Factors; Degradation impurity; vysokoúčinná kapalinová chromatografie; Formaldehyde